Reliability of Estimation Pile Load Capacity Methods - Yudhi Lastiasih; Indra Djati Sidi (Institute for Research and Community Services, Institut Teknologi Bandung, 2014)
None of numerous previous methods for predicting pile capacity is known how accurate any of them are when compared with the actual ultimate capacity of piles tested to failure. The author's of the present paper have conducted such an analysis, based on 130 data sets of field loading tests. Out of these 130 data sets, only 44 could be analysed, of which 15 were conducted until the piles actually reached failure. The pile prediction methods used were: Brinch Hansen's method (1963), Chin's method (1970), Decourt's Extrapolation Method (1999), Mazurkiewicz's method (1972), Van der Veen's method (1953), and the Quadratic Hyperbolic Method proposed by Lastiasih et al. (2012). It was obtained that all the above methods were sufficiently reliable when applied to data from pile loading tests that loaded to reach failure. However, when applied to data from pile loading tests that loaded without reaching failure, the methods that yielded lower values for correction factor N are more recommended. Finally, the empirical method of Reese and O'Neill (1988) was found to be reliable enough to be used to estimate the Qult of a pile foundation based on soil data only.